Pengaruh Pendekatan Pembelajaran Berdiferensiasi terhadap Hasil Belajar Matematika Siswa Kelas IV SDN Gugus XIX Kota Bengkulu - Srikandi, Aisyah Mania; Agusdianita, Neza; Kurniawati, Ike; Supriatna, Irfan; Yusnia, Yusnia (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
The background of this research is the desire to address complex problems in mathematics learning within the Merdeka Curriculum, especially those stemming from teachers lack of understanding of students initial characteristics, which impacts student learning outcomes.This study aims to determine the effect of the differentiated learning approach on the mathematics learning outcomes of fourth-grade students at gugus state primary school XIX Bengkulu City. This research employs a quantitative approach with a quasi-experimental method. The research design used is the matching only pretest-posttest control group. The sampling technique applied in this study is cluster random sampling, consisting of two groups: the experimental group, which implements the differentiated learning approach, and the control group, which follows the scientific approach. The data from this study were analyzed using statistical tests. The average posttest scores of the experimental and control groups were 79,10 and 69,23, respectively. The statistical test results indicate that the sig. (2-tailed) value for the posttest is 0,000 (0,000 < 0,05), and the t-value is 4,269, which is greater than the t-table value of 1,680. This indicates a significant difference in the posttest mean scores between the experimental and control groups Which is caused by the different treatments applied to each group. Based on these findings, it can be concluded that the differentiated learning approach has a significant effect on the mathematics learning outcomes of fourth-grade students at gugus state primary school XIX Bengkulu City. Therefore, this approach can be an effective strategy to enhance students conceptual understanding of mathematics and improve the quality of learning in elementary schools. Penelitian ini dilatarbelakangi oleh keinginan untuk mengatasi permasalahan kompleks dalam pembelajaran matematika dalam Kurikulum Merdeka, terutama yang bersumber dari kurangnya pemahaman guru terhadap karakteristik awal siswa, yang berdampak pada hasil belajar siswa. Tujuan penelitian ini untuk mengetahui pengaruh pendekatan pembelajaran berdiferensiasi terhadap hasil belajar matematika siswa kelas IV SDN Gugus XIX Kota Bengkulu. Jenis penelitian yang digunakan adalah kuantitatif dengan metode eksperimen kuasi. Desain  yang digunakan adalah the matching only pretest-posttest control group. Teknik pengambilan sampel dalam penelitian ini yaitu cluster random sampling  dengan sampel terdiri dari dua kelompok, yaitu kelompok eksperimen yang menerapkan pendekatan pembelajaran berdiferensiasi dan kelompok kontrol dengan pendekatan saintifik. Data dari penelitian ini dianalisis menggunakan uji statistik. Nilai rata-rata posttest kelompok eksperimen dan kontrol adalah sebesar 79,10 dan 69,23. Hasil penelitian menunjukkan bahwa nilai sig. (2-tailed) pada posttest adalah 0,000 (0,000 < 0,05), serta nilai thitung sebesar 4,269 lebih besar dari ttabel 1,680 yang artinya terdapat perbedaan yang signifikan nilai rata-rata posttest antara kelompok eksperimen dan  kontrol yang disebabkan adanya perlakuan yang berbeda pada setiap kelompok. Berdasarkan hasil tersebut, maka dapat disimpulkan bahwa terdapat pengaruh pendekatan pembelajaran berdiferensiasi terhadap hasil belajar matematika siswa kelas IV SDN Gugus XIX Kota Bengkulu. Oleh karena itu, pendekatan pembelajaran berdiferensiasi dapat menjadi strategi efektif dalam meningkatkan pemahaman konsep matematika dan kualitas pembelajaran di sekolah dasar.